Anti-microbial studies of alkaloids from "Botolan", securinaga virosa. - Giner, Gretchen Bo-peep G.
Previous studies that "Botolan" contains alkaloids and has antimicrobial activity. Herbolarios also claim that the can be used as a decoction in cleansing wounds. (p)A Phytochemical test, using Culvenor-Fitsgerald Method confirms the presence of alkaloid in "Botolan" and this was isolated using standard-acid base method. (p)The crude extract was examined for its antimicrobial activity against Staphyloccocus aureus, Bacilus subtilis, Eschericia coli, Pseudomonas aeruginosa and Candida albicans. Results indicated that it was active only to S. aureus and P. aerugenosa. (p)The isolated crude alkaloid was purified by Vacuum Liquid Chromatography using different ratios of n-hexane, dichloromethane (DCM) and ethyl acetate (EA) in increasing polarities as solvent systems. The complexities of the different fractions were monitored by TLC and antimicrobial activities of the different fractions were also tested. (p)The TLC results using DCM:EA (1:1) as solvent system, showed that among the six combined fractions, only S28-F6.2 (Rf = 0.52) exhibited antimicrobial activity against P. aeruginosa, E. coli and B. subtilis.